INDIKATOR EKONOMI REGIONAL DAN PERILAKU INVESTOR DI JAWA BARAT - Ganjar Suherman; Muhammad Iqbal Noer Firdaus (Jurnal Riset Ilmu Ekonomi, 2021)
One of development indicator in the country is highlighted by economic growth. For instance, economic growth is a value-added increase in count period which compared with the previous period. Economic growth calculations are calculated by several components which one of them is investment instrument. However, The study aims to explore investment instrument in West Java Province that influenced by several variables which are credit (capital and consumption), economic growth and interest rate (BI rate). The study supported by secunder data of time series in 2009-2019 which sourced by Badan Pusat Statistik Jawa Barat (Statistic Center Bureau of West Java) and Indonesia Bank. The result of regress data explains all independent variable affect investment instrument, positifly significant.